Psychosocial Predictors of Sexual HIV Transmission Risk Behavior among HIV-Positive Adults with a Sexual Abuse History in Childhood - Sikkema, Kathleen J. (Arch Sex Behav, 2007)
Childhood sexual abuse (CSA) is associated with HIV sexual risk behavior. Although many psychosocial correlates of sexual risk among HIV-positive persons have been identified, studies predicting continued risk among HIV-positive adults with histories of CSA are limited. This cross-sectional study identified variables predictive of sexual transmission risk behavior among an ethnically diverse sample of 256 HIV-positive adults (women and men who have sex with men; MSM) with CSA histories. Participants were assessed for trauma symptoms, shame related to HIV and sexual trauma, substance use, coping style, and sexual risk behavior. Logistic regression analyses were conducted to identify variables predictive of unprotected sexual behavior in the past 4 months. Unprotected sex was significantly associated with substance use and trauma-related behavioral difficulties among women and men, and less spiritual coping among men. Unprotected sex with HIV negative or serostatus unknown partners was significantly associated with greater trauma-related behavioral difficulties, more HIV-related shame, and fewer active coping strategies. Thus, trauma symptoms, shame, coping style, and substance use were significantly associated with sexual risk behavior among HIV-positive adults with histories of CSA, with models of prediction differing by gender and partner serostatus. HIV prevention intervention for persons with HIV and CSA histories should address trauma-related behavioral difficulties and enhance coping skills to reduce sexual transmission risk behavior.